Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's find the antiderivative [tex]\( F(x) \)[/tex] of the given function [tex]\( f(x) = x^3 - 3x^{-4} + 4 \)[/tex], and ensure it satisfies the condition [tex]\( F(1) = 1 \)[/tex].
Step 1: Integrate the function [tex]\( f(x) \)[/tex] to find the indefinite integral [tex]\( F(x) \)[/tex]:
[tex]\[ \int f(x) \, dx = \int (x^3 - 3x^{-4} + 4) \, dx \][/tex]
To integrate term by term:
1. The antiderivative of [tex]\( x^3 \)[/tex] is:
[tex]\[ \int x^3 \, dx = \frac{x^4}{4} \][/tex]
2. The antiderivative of [tex]\( -3x^{-4} \)[/tex] is:
[tex]\[ \int -3x^{-4} \, dx = -3 \int x^{-4} \, dx = -3 \left( -\frac{1}{3} x^{-3} \right) = x^{-3} \][/tex]
3. The antiderivative of [tex]\( 4 \)[/tex] is:
[tex]\[ \int 4 \, dx = 4x \][/tex]
Combining these results, we get the general antiderivative as:
[tex]\[ F(x) = \frac{x^4}{4} + 4x + x^{-3} + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
Step 2: Use the initial condition [tex]\( F(1) = 1 \)[/tex] to determine the constant [tex]\( C \)[/tex]:
Substitute [tex]\( x = 1 \)[/tex] and [tex]\( F(1) = 1 \)[/tex] into the general antiderivative:
[tex]\[ 1 = \frac{1^4}{4} + 4(1) + 1^{-3} + C \][/tex]
Simplify the equation:
[tex]\[ 1 = \frac{1}{4} + 4 + 1 + C \][/tex]
[tex]\[ 1 = 5.25 + C \][/tex]
[tex]\[ C = 1 - 5.25 \][/tex]
[tex]\[ C = -4.25 \][/tex]
[tex]\[ C = -\frac{17}{4} \][/tex]
Step 3: Write the complete antiderivative with the determined constant [tex]\( C \)[/tex]:
[tex]\[ F(x) = \frac{x^4}{4} + 4x + x^{-3} - \frac{17}{4} \][/tex]
So, the antiderivative [tex]\( F(x) \)[/tex] that satisfies [tex]\( F(1) = 1 \)[/tex] is:
[tex]\[ F(x) = \frac{x^4}{4} + 4x + x^{-3} - \frac{17}{4} \][/tex]
Step 1: Integrate the function [tex]\( f(x) \)[/tex] to find the indefinite integral [tex]\( F(x) \)[/tex]:
[tex]\[ \int f(x) \, dx = \int (x^3 - 3x^{-4} + 4) \, dx \][/tex]
To integrate term by term:
1. The antiderivative of [tex]\( x^3 \)[/tex] is:
[tex]\[ \int x^3 \, dx = \frac{x^4}{4} \][/tex]
2. The antiderivative of [tex]\( -3x^{-4} \)[/tex] is:
[tex]\[ \int -3x^{-4} \, dx = -3 \int x^{-4} \, dx = -3 \left( -\frac{1}{3} x^{-3} \right) = x^{-3} \][/tex]
3. The antiderivative of [tex]\( 4 \)[/tex] is:
[tex]\[ \int 4 \, dx = 4x \][/tex]
Combining these results, we get the general antiderivative as:
[tex]\[ F(x) = \frac{x^4}{4} + 4x + x^{-3} + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
Step 2: Use the initial condition [tex]\( F(1) = 1 \)[/tex] to determine the constant [tex]\( C \)[/tex]:
Substitute [tex]\( x = 1 \)[/tex] and [tex]\( F(1) = 1 \)[/tex] into the general antiderivative:
[tex]\[ 1 = \frac{1^4}{4} + 4(1) + 1^{-3} + C \][/tex]
Simplify the equation:
[tex]\[ 1 = \frac{1}{4} + 4 + 1 + C \][/tex]
[tex]\[ 1 = 5.25 + C \][/tex]
[tex]\[ C = 1 - 5.25 \][/tex]
[tex]\[ C = -4.25 \][/tex]
[tex]\[ C = -\frac{17}{4} \][/tex]
Step 3: Write the complete antiderivative with the determined constant [tex]\( C \)[/tex]:
[tex]\[ F(x) = \frac{x^4}{4} + 4x + x^{-3} - \frac{17}{4} \][/tex]
So, the antiderivative [tex]\( F(x) \)[/tex] that satisfies [tex]\( F(1) = 1 \)[/tex] is:
[tex]\[ F(x) = \frac{x^4}{4} + 4x + x^{-3} - \frac{17}{4} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.